2019
DOI: 10.1038/s41467-019-12652-1
|View full text |Cite
|
Sign up to set email alerts
|

Interval breast cancer is associated with other types of tumors

Abstract: Breast cancer (BC) patients diagnosed between two screenings (interval cancers) are more likely than screen-detected patients to carry rare deleterious mutations in cancer genes potentially leading to increased risk for other non-breast cancer (non-BC) tumors. In this study, we include 14,846 women diagnosed with BC of which 1,772 are interval and 13,074 screen-detected. Compared to women with screen-detected cancers, interval breast cancer patients are more likely to have a non-BC tumor before (Odds ratio (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 58 publications
2
31
3
Order By: Relevance
“… 3 , 4 , 5 When the relationship between method of breast cancer detection and outcome is provided, the effect size is rather small. 6 In this study, we used a population-based cancer registry to compare the biology and outcomes of SBC with those of IBC.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 , 5 When the relationship between method of breast cancer detection and outcome is provided, the effect size is rather small. 6 In this study, we used a population-based cancer registry to compare the biology and outcomes of SBC with those of IBC.…”
Section: Introductionmentioning
confidence: 99%
“…This may partly explain our findings on the particularly worse prognosis of BCa-2 after ovarian cancer. A recent study also showed that breast cancer developed between two screenings, a known type of worse prognosis, is more likely to have a non-breast malignancy before and after breast cancer diagnosis, potentially through rare deleterious mutations in cancer genes [ 12 ]. Further research is warranted to understand mutations leading to BCa-2 after other malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…This is partly attributable to intensive cancer treatment for the first malignancy (e.g., radiotherapy [8] and chemotherapy [1]), as well as certain lifestyle (e.g. smoking [9,10]) and genetic factors [11,12] that predisposed the individual to both first and second malignancies. Compared with the general population, high-dose chest radiation or exposure to alkylator or anthracycline was associated with drastically increased risk of subsequent breast cancer among childhood cancer survivors [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Mammography X‐ray image is able to detect 70%–80% of breast cancers; the remnants (20%–30%) are detected between screen intervals, and unfortunately are of the more aggressive type, namely triple negative. [ 271 ] For PDAC, symptoms are not specific, which causing advanced metastatic stage upon diagnosis. [ 54 ] Survival from cancer can impose other health issues in aged populations.…”
Section: Challenges In Regard To Tumors Of Solid Organs and Therapymentioning
confidence: 99%